Construction of Ethic Code of Public Accountant in Perspective of Value of Bugis Culture - Muhammad Aras Prabowo; Hadri Mulya (AIBPM Publisher, 2018)
This study aims to construct the code of ethics for public accountants in perspective of bugis culture value. The focus of this study to formulate the code of ethics for public accountants on perspective of bugis culture value. The approach used was the interpretive-constructivism paradigm with the method of spradley-style etnography. The data collection follows the creswell and spradley-etnographic interview techniques. The result of this study succeeded formulate the code of ethics for public accountants on perspective of bugis culture: 1). Lempu sustained by ada tongeng, getteng, asitinajang, amaccang, and warani, 2). Pacce generated from sipakatau, sipakalebbi, sipakainge, sipatokkong, and sipakarennu, 3). Reso, and 4). Appesona ri dewata seuwwae as instrument in actualitation the code of ethics, because a code of ethics will no exist if there is no practice on it. The conclusion of this study that the values have been disclosed, crystallized by the researcher as a code of ethics for public accountants on bugis cultural perspective to improve compliance on code of ethics for public accountants.